2019
DOI: 10.1029/2018ja026182
|View full text |Cite
|
Sign up to set email alerts
|

Helios Observations of Quasiperiodic Density Structures in the Slow Solar Wind at 0.3, 0.4, and 0.6 AU

Abstract: Following previous investigations of quasiperiodic plasma density structures in the solar wind at 1 AU, we show using the Helios1 and Helios2 data their first identification in situ in the inner heliosphere at 0.3, 0.4, and 0.6 AU. We present five events of quasiperiodic density structures with time scales ranging from a few minutes to a couple of hours in slow solar wind streams. Where possible, we locate the solar source region of these events using photospheric field maps from the Mount Wilson Observatory a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

12
61
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
4
3
1
1

Relationship

5
4

Authors

Journals

citations
Cited by 39 publications
(73 citation statements)
references
References 136 publications
(179 reference statements)
12
61
0
Order By: Relevance
“…They are shown in Figure 8a and b by dashed vertical lines. Such density structures were noticed in past in situ measurements taken near 1 au (Viall, et al 2008), in Helios data between 0.3 and 0.6 au (Di Matteo et al 2019) and separately in the spectral analysis of COR2A imagery (Viall, & Vourlidas 2015). Combined STA and PSP observations allow, for the first time, investigation of the origin of individual features.…”
Section: Tracing Density Structures From Psp Back To the Sunsupporting
confidence: 58%
“…They are shown in Figure 8a and b by dashed vertical lines. Such density structures were noticed in past in situ measurements taken near 1 au (Viall, et al 2008), in Helios data between 0.3 and 0.6 au (Di Matteo et al 2019) and separately in the spectral analysis of COR2A imagery (Viall, & Vourlidas 2015). Combined STA and PSP observations allow, for the first time, investigation of the origin of individual features.…”
Section: Tracing Density Structures From Psp Back To the Sunsupporting
confidence: 58%
“…Our results indicate that the quasiperiodic mesoscale structures within the SIR were previously structures in the uncompressed slower solar wind ahead and are consistent with the belief that these structures are created at the time of solar wind generation. Evidence for a solar source of periodic density structures includes remote sensing of these structures down to a few solar radii (Viall & Vourlidas, 2015;Viall et al, 2010) and in situ studies using both Helios (Di Matteo et al, 2019) and L1 observations (Kepko et al, 2016;Viall, Spence, and Kasper 2009). Kepko et al (2016) recently examined a 12-hr interval of solar wind that contained periodic density structures, which previously had been studied as driving magnetospheric pulsations (Kepko & Spence, 2003).…”
Section: Journal Of Geophysical Research: Space Physicsmentioning
confidence: 99%
“…It is important to note that these periodic density structures in the solar wind are not propagating waves. Rather, they are coherent mesoscale structures created very early in the formation of the solar wind, which then advect outward in quasi pressure balance (DeForest et al, 2018;Di Matteo et al, 2019;Kepko et al, 2016;Viall & Vourlidas, 2015;Viall, Spence, & Kasper, 2009;Viall, Spence, Vourlidas, & Howard, 2010).…”
Section: Introductionmentioning
confidence: 99%
“…Though relating terrestrial geomagnetic pulsations to solar oscillations is an intriguing possibility, subsequent work addressing whether the solar wind contains imprints of solar oscillation modes has yielded conflicting results (Kepko et al 8 ). Recent studies have reported the presence of quasi-periodic density structures in the solar corona (Viall and Vourlidas) 23 , in the solar wind from 0.3 to 0.6 AU (Di Matteo et al) 24 , and at L1 (Kepko et al) 25 . These periodicities are in the range 60-130 mins, and our results (25-27 minutes) do not compare favourably.…”
Section: Discussion: a Possible Source Of The Ripplesmentioning
confidence: 99%